If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 24 = 13x + -20 Reorder the terms: 24 + 6x = 13x + -20 Reorder the terms: 24 + 6x = -20 + 13x Solving 24 + 6x = -20 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 24 + 6x + -13x = -20 + 13x + -13x Combine like terms: 6x + -13x = -7x 24 + -7x = -20 + 13x + -13x Combine like terms: 13x + -13x = 0 24 + -7x = -20 + 0 24 + -7x = -20 Add '-24' to each side of the equation. 24 + -24 + -7x = -20 + -24 Combine like terms: 24 + -24 = 0 0 + -7x = -20 + -24 -7x = -20 + -24 Combine like terms: -20 + -24 = -44 -7x = -44 Divide each side by '-7'. x = 6.285714286 Simplifying x = 6.285714286
| 2x+7=30 | | 3x+5y=47 | | 8x-16+x^2=0 | | x^2=-24x-144 | | 70a^2+3a-1=0 | | 4x-3(2x-9)=-(9-x) | | y^2=2y-1 | | y(3y+1)(4y-1)= | | 0.23*5=2.3*0.5 | | 24-36x=12(2-3x) | | 3x+70=9x+12 | | 16(2x-3)=32x-19 | | 45=b(b-4) | | 3w^2-10=13w | | 3(6x+2)=18x+5 | | 9y^2-2y-1= | | 8ac-2ad+4bc-bd= | | 39y^2-3y-8= | | 39y^2-3y-8=0 | | 36=b(b-5) | | 3b^2-10=13b | | v^2+2v-35=0 | | a^2+40a=0 | | (x^2-0.2454)(.2-x)=x^2 | | (x^3-0.2454)(.2-x)=x^2 | | (0.000018)(.2-x)=x^2 | | 4(x-1)=22 | | b^2-b-2=0 | | 5x+32=15x-78 | | p-36=-33 | | 5w^2=180 | | 5w^2-180=0 |